The Nature of Truth An updated approach to the meaning of truth ascriptions - Frapolli, Maria Jose.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
The book offers a characterization of the meaning and role of the notion of truth in natural languages and an explanation of why, in spite of the big amount of proposals about truth, this task has proved to be resistant to the different analyses. The general thesis of the book is that defining truth is perfectly possible and that the average educated philosopher of language has the tools to do it. The book offers an updated treatment of the meaning of truth ascriptions from taking into account the latest views in philosophy of language and linguistics.
1. some preliminary issues -- 2. Syntax: Playing with building blocks -- 3. The meaning and content of truthascriptions -- 4. What do we do with truth ascriptions -- 5. The Liar paradox (and other Logico-Semantic issues) -- 6. What do you mean by (3z (BRedundancy(3y(B? -- 7. Obvious answers for ready-made objections -- 8. References -- 9. Index.s
Keywords: Philosophy (General).; Logic; Linguistics -- Philosophy; Pragmatism; Semantics; Philosophy; Philosophy of Language; Pragmatism; Semantics; Logic